The Issue of Embryo Implantation in Women during the Coronavirus Outbreak: An Overview: Embryo Implantation and Coronavirus - Rezaee, Delsuz; Rezaee, Hanieh; Bastaminejad, Saiyad; Bahrami, Yadollah; Salehi, Mohammad (Novelty in Biomedicine, 2021)
Abstract The Coronavirus is a major health problem nowadays, which affects people’s lifestyle. This pandemic virus shared a variety of phenomena in case of symptoms and side effects. One of the major issues regarding novel coronavirus is the effect of infection on pregnancy which accounts for an essential process of human life. Considering the pathogenesis of Coronavirus, overexpression of inflammatory cells and cytokines accounts a pivotal step in the development of symptoms. The over-expressed cytokines in response to covid-19 infection would render the inflammation and disruption of the immune system and tissue damage. Like coronavirus infection, implantation the main step of a successful pregnancy, activates the inflammatory cells and cytokines. The association of infection with pregnancy raises the concern about the effect of covid-19 on embryos and giving normal birth, especially in women who decide to get pregnant or are in the pregnancy period. The current review focused on immune system responses to the Coronavirus and comparison with immune system activation during implantation. It concluded that further laboratory research and studies are needed to better understand and draw general conclusions about the role of the virus in embryo implantation.